Mouse moves house - Cox, Phil Roxbee; Cartwright, Stephen; Tyler, Jenny (Tulsa, Okla. : EDC, 2003)
Mouse moves to a new house with the help of a least-likely friend.
"A phonics reader"--Cover.
Lift-the-flap pages.
2.9.
2.9
K-3
Keywords: Toy and movable books -- Specimens; Mice -- Fiction; Stories in rhyme; Toy and movable books; Mice -- Fiction; Stories in rhyme; Toy and movable books